2019
DOI: 10.1142/s0217751x1950218x
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic oscillators in new type of the extended uncertainty principle

Abstract: We present the exact solutions of one-dimensional Klein–Gordon and Dirac oscillators subject to the uniform electric field in the context of the new type of the extended uncertainty principle using the displacement operator method. The energy eigenvalues and eigenfunctions are determined for both cases. For the Klein–Gordon oscillator case, the wave functions are expressed in terms of the associated Laguerre polynomials and for the Dirac oscillator case, the wave functions are obtained in terms of the confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Instead of building a larger collider, the energy limitation problem can be overcome with the help of performing passive experiments using interferometry. Numerous proposals are there in this regime [19,20,21,22,23,24,25,26,27,28]. However, to the best of knowledge of present authors, none of them had yet been carried out.…”
Section: Introductionmentioning
confidence: 93%
“…Instead of building a larger collider, the energy limitation problem can be overcome with the help of performing passive experiments using interferometry. Numerous proposals are there in this regime [19,20,21,22,23,24,25,26,27,28]. However, to the best of knowledge of present authors, none of them had yet been carried out.…”
Section: Introductionmentioning
confidence: 93%
“…[51][52][53] One of these formulations is derived from a a) Electronic mail: bruno.costa@ifsertao-pe.edu.br b) Electronic mail: cardoso.genilson@outlook.com c) Electronic mail: ignacio.sebastian@ufba.br translation operator that causes non-additive displacements of the type Tγ (ε)|x = |x + (1 + γx)ε , being γ a deformation parameter with inverse length dimension. [54][55][56][57][58][59][60][61][62][63][64][65][66][67] This translation operator leads to a position-dependent linear momentum operator pγ that generates non-additive translations. Consequently, the particle mass is a function of the position controlled by the parameter γ.…”
Section: Introductionmentioning
confidence: 99%
“…In the displacement-operator formalism, the time-independent Schrödinger equation can be expressed using a deformed derivative operator D γ = (1 + γx)d/dx, which results physically equivalent to introduce a particle with a PDM. Typical problems of quantum mechanics have been solved within this approach: infinite and finite square potential wells, [54][55][56] quantum dots and wells, 57,58 quasiperiodic 59 and Coulomb-like potentials, 60 harmonic oscillator, [61][62][63][64][65] Dirac fermions in graphene 66 and two dimensional electron gas. 67 It can be shown that the energy spectrum of the deformed harmonic oscillator corresponds to the Morse oscillator, i.e., an anharmonic oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…Along the lines outlined previously, much work has been done either modifying the Heisenberg uncertainty relations [1][2][3][4], restudying the classical-quantum mechanics transition [23][24][25][26][27], modifying quantum mechanics using quantum groups [28] or using arguments from noncommutative geometry [29][30][31][32][33][34][35][36][37][38][39][40][41][42] and related arguments [3,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%